Ceramide metabolism and cardiovascular risk factors: insights into therapeutic strategies - Yang, Shouyi; Wu, Yongxin (Frontiers in Cardiovascular Medicine, 2025)
Ceramides are components of sphingolipid metabolism and have been linked to cardiovascular disease (CVD) risk factors, including hypertension, insulin resistance, dyslipidemia and chronic kidney disease. Ceramide expression has been extensively studied but individual variability, species differences and regulatory mechanisms characterizing underlying relationships remain unclear. The current review analyzes roles of ceramides in the onset and progression of CVD and its risk factors. Diverse ceramide expression profiles are highlighted and recommendations for standardization of ceramide studies given. Ceramides are multifunctional and contribute to organ damage through dysregulated homeostasis during pathological processes. The current work emphasizes the importance of detecting ceramide imbalance and accounting for individual differences as a novel approach to metabolic research. Such a focus may enhance CVD management and give insights into ceramide-related pathologies.